Functional outcome of manipulation under anaesthesia for the treatment of frozen shoulder: Functional outcome of MUA for frozen shoulder (Journal of Fatima Jinnah Medical University, 2020)
Background: Frozen shoulder is defined as painful progressive loss of shoulder movements with unknown etiology. It is a self-limiting disease with the natural history of 18-30 months but with residual pain and restriction of shoulder movement. Its incidence is 2-5%. Various treatment modalities include benign neglect, physical therapy, non-steroidal anti-inflammatory medications, oral glucocorticoids, distention arthrography, intra articular steroid injections, closed manipulation under anaesthesia (MUA) and arthroscopic release of joint capsule. MUA regarding pain control and range of motion is safe, yields immediate results and is very cost effective. The purpose of this study was to ascertain the functional outcome of manipulation under anaesthesia and physiotherapy for the treatment of frozen shoulder in term of safety, cost effectiveness and immediate results.Patients and Methods: In the 6 months study period, 50 patients with adhesive capsulitis were included by non-probability purposive sampling. Manipulation of shoulders was done under general anaesthesia and after the MUA intra articular injection of a mixture of corticosteroid and local anaesthetic was injected. Postoperatively, all patients underwent physiotherapy. Functional outcome was measured using Shoulder Pain and Disability Index (SPADI) preoperatively and postoperatively at 1st, 2nd and 3rd week follow up.Results: Out of 50 patients, 32 (64%) were females and 18 (36%) were males having female to male ratio of 1.8:1. Average age was 51 years and average duration of symptoms preceding to MUA was 4 months and 27 days. The average pain score decreased from 92.52% to 18.08% and the average disability score reduced from 95% to 17.10%, both at 3rd week postoperative follow up. There were no procedure-related complications.Conclusion: Manipulation under anaesthesia along with physiotherapy diminishes pain and disability, improves range of motion and expedites early recovery of function in patients having frozen shoulder.
Keywords: Frozen shoulder; Physiotherapy; Manipulation under anaesthesia